A Comparative Study of McKenzie Back Program and Conventional Physiotherapy in Relieving Backache due to Lumbar Disc Prolapse - Aqeel Moazzam, Arif Kaleem, Waqas Ali, Zohaib Nadeem, Nisar Ahmad, Imran Ahmad, Abdul Aziz, (Pakistan Journal of Medical & Health Sciences, 2023)
Introduction: Low Back Pain (LBP) is considered as one of the commonest problems, in which pain felt in the lumbosacral spinal and paraspinal regions which encompass the buttocks and upper thigh. Objectives: The main objective of the study is to find the comparison between McKenzie back program and conventional physiotherapy in relieving backache due to lumbar disc prolapse. Material and methods: This cross sectional study was conducted in Rashid Latif Medical College Lahore during January 2022 to June 2022. Persons having MRI and previously diagnosed as Disc herniation or Lumbar disc herniation LDH or Prolapsed Lumbar intervertebral disc (PLID) were also enrolled and screened for the second time, the persons who had no MRI were advised to perform with proper justification. Results: Data was collected from 40 patients. There were 22 females and 18 males. Both groups were matched as regards age, gender, weight, height, and BMI. ODI scores showed a significant decrease in both groups post-treatment (p = 0.001) indicating a decrease of functional disability. The percentage of decrease in Oswestry scores was higher in group B than group A (6.87% versus 4.82%). Practical Implication: This study will be helpful in reducing pain, increasing lumbar spine mobility and decreasing disability. Conclusion: It is concluded that McKenzie back program is more effective in reducing pain, increasing lumbar spine mobility and decreasing disability than conventional physiotherapy and stretching exercises in patients with backache due to lumbar disc prolapse. Keywords: Effective, Backache, Pain, Disability